2017
DOI: 10.2196/mhealth.7628
|View full text |Cite
|
Sign up to set email alerts
|

Health App Possession Among Smartphone or Tablet Owners in Hong Kong: Population-Based Survey

Abstract: BackgroundHealth apps are increasingly used with important implications for health. Hong Kong is one of the most technologically advanced and connected cities—smartphone ownership and Internet access rates are among the highest in the world.ObjectiveWe investigated the prevalence of health app possession and related sociodemographic factors and health behaviors among smartphone or tablet owners in Hong Kong.MethodsA territory-wide population-based dual (landline and mobile) telephone survey was conducted in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 33 publications
5
70
2
2
Order By: Relevance
“…Our study however showed that their needs are not being catered for at present. Although studies have demonstrated the ability of technology to improve access to care, inequality is still high between younger and older and more and less deprived populations . We need apps with elderly friendly features, as the elderly population is capable of adopting mHealth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study however showed that their needs are not being catered for at present. Although studies have demonstrated the ability of technology to improve access to care, inequality is still high between younger and older and more and less deprived populations . We need apps with elderly friendly features, as the elderly population is capable of adopting mHealth.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have demonstrated the ability of technology to improve access to care, inequality is still high between younger and older and more and less deprived populations. 13 We need apps with elderly friendly features, 24 as the elderly population is capable of adopting mHealth. While e-commerce and m-commerce have grown tremendously in China, mHealth presents more challenges in terms of pricing and regulations.…”
Section: Populations Most In Need Often Do Not Have Access To Technmentioning
confidence: 99%
See 1 more Smart Citation
“…FHInTS was a regular periodic probability-based telephone survey of the general Hong Kong public designed to assess the opinions and behaviors on family health, information use and health communication. To date, five waves of FHInTS had been conducted and details were reported elsewhere [23,24]. The current wave was conducted from January to August 2016.…”
Section: Study 1: the Hong Kong Family And Health Information Trendsmentioning
confidence: 99%
“…Çalışmamızda adımsayar gibi uygulamaların kullanım sıklığı %24 olarak bulunmuş olup egzersiz sonrasında ikinci sıklıkta kullanılan uygulama olarak tespit edildi. Shen C ve arkadaşlarının yaptığı çalışmada günlük sağlık kayıtlarını inceleyebilecekleri kilo takibi (%43) gibi uygulamalar ikinci sıklıkla kullanılmakta olarak saptanmıştır (9).…”
Section: Introductionunclassified